The Transformation of Research in the South : Policies and outcomes - David O'Brien (IRD Éditions, 2019)
Profound transformations are affecting the research systems around the world. We witness the emergence of new or restructured organizations to steer public research or promote innovation, new programmatic directions within these organizations, increased funding dedicated to research in academic settings, and new domestic and international partnerships and collaborations. A multiplicity of organizations and funding sources have appeared, creating a complex web where resources circulate along with knowledge in ways that are reshaping research systems in the South. This book gathers a large sample of these changes presented during a symposium organized by IDRC, IRD, IFRIS, and OECD, seeking to better understand their institutional, political and economic drivers. These cases document the building of scientific capacity and the broader use of results from scientific research and presents lessons for public policy. A large variety of case studies of specific research organizations and comparative analysis of the wider research system are presented in Asia, Africa, and Latin America.